Evitable Conflicts, Inevitable Technologies? The Science and Fiction of Robotic Warfare and IHL. (February 2018) - Kerr, Ian; Szilagyi, Katie
This article contributes to a special symposium on science fiction and international law, examining the blurry lines between science and fiction in the policy discussions concerning the military use of lethal autonomous robots. In response to projects that attempt to build military robots that comport with international humanitarian law [IHL], we investigate whether and how the introduction of lethal autonomous robots might skew international humanitarian norms. Although IHL purports to be a technologically-neutral approach to calculating a proportionate, discriminate, and militarily necessary response, we contend that it permits a deterministic mode of thinking, expanding the scope of that which is perceived of as "necessary" once the technology is adopted. Consequently, we argue, even if lethal autonomous robots comport with IHL, they will operate as a force multiplier of military necessity, thus skewing the proportionality metric and amplifying new forms of destructive, lethal force.